1999
DOI: 10.1034/j.1600-0420.1999.770211.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic macular edema, Risk factors and concomitants

Abstract: ABSTRACT.Purpose: To investigate the systemic and ocular factors associated with diffuse macular edema in patients with diabetic retinopathy (DR) and compare with patients with focal or no macular edema. Methods: From 160 consecutive patients with DR, we obtained medical and ocular histories, blood pressure and visual acuity. Macular edema was determined by biomicroscopy and stereoscopic fundus photography. Fluorescein angiography was used in the characterization of its leakage, and the vitreoretinal relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 27 publications
2
70
1
Order By: Relevance
“…Lopes de Faria and co-workers have shown that adult-onset diabetes mellitus, high blood pressure, cardiovascular disease, vitreomacular adhesion and advanced diabetic retinopathy increase the risk for diabetic macular edema (28) . Although our study did not evaluate macular edema as an endpoint, our data showed that visual acuity was directly influenced by the severity of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Lopes de Faria and co-workers have shown that adult-onset diabetes mellitus, high blood pressure, cardiovascular disease, vitreomacular adhesion and advanced diabetic retinopathy increase the risk for diabetic macular edema (28) . Although our study did not evaluate macular edema as an endpoint, our data showed that visual acuity was directly influenced by the severity of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dilatation of the retinal arterioles has been shown to occur before the development of diabetic macular oedema 96 whereas reversal of vasopermeability and oedema following pan-retinal laser photocoagulation is associated with retinal vasoconstriction. 64 Supporting evidence for involvement of abnormal retinal blood flow in oedema comes from studies that indicate diffuse macular swelling is more than three times greater in diabetic patients with hypertension 97 and that reducing blood pressure protects against this end point. 4 …”
Section: Macular Oedemamentioning
confidence: 99%
“…Several studies have pointed out the increased frequency of systemic cardiovascular disorders (CVDs) in CMO due to diabetic retinopathy, central retinal vein occlusion, and post intraocular surgery. [4][5][6][7][8] Recent reports showed that systemic microvascular damage, which is a risk factor for developing CVD, was associated with inflammatory and diabetic CMO.…”
Section: Introductionmentioning
confidence: 99%